2021
DOI: 10.3389/fenvs.2021.657608
|View full text |Cite
|
Sign up to set email alerts
|

Market Costs and Financing Options for Grassland Carbon Sequestration: Empirical and Modelling Evidence From Qinghai, China

Abstract: Asia’s grasslands provide livelihoods for some of the region’s poorest people. Widespread grassland degradation reduces the resilience and returns to herding livelihoods. Reversing degradation and conserving grasslands could not only improve herders’ situation, but also make a huge contribution to mitigating climate change by sequestering carbon in soils. However, the means for reaching each of these objectives are not necessarily the same. To realize this potentially huge dual livelihood/climate change mitiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Another study found that, within China's cap and trade mechanism, economic costs for grassland mitigation measures could be achieved between USD -6.52 to 3.78 t CO2eq (with negative values indicating another valuable positive PAPER ACCEPTED. PREPRINT VERSION effects aside carbon sequestration) and could be traded at market values between USD 12.7 and 30.90 t CO2eq (Wilkes et al, 2021).…”
Section: Exploratory Analysesmentioning
confidence: 99%
“…Another study found that, within China's cap and trade mechanism, economic costs for grassland mitigation measures could be achieved between USD -6.52 to 3.78 t CO2eq (with negative values indicating another valuable positive PAPER ACCEPTED. PREPRINT VERSION effects aside carbon sequestration) and could be traded at market values between USD 12.7 and 30.90 t CO2eq (Wilkes et al, 2021).…”
Section: Exploratory Analysesmentioning
confidence: 99%